장애인 정보격차 해소를 위한 정보통신 보조기기 활용방안 연구 - 김정호; 구교준; 서준교 (한국감성과학회, 2010)
The purposes of this study are to investigate and analyze the level of information and the state of digital divide of the disabled by surveying the demand for information and communication assistive devices, and to provide basic data for plans on the development and utilization of information and communication assistive devices. In order to understand the actual condition and the state of digital divide of persons with disabilities, the differences of possession and accessibility of information technology devices, usage ability, and utilization were analyzed according to the disability profile by using the T-test. The results show that there are significant differences (T=-2.510*) of possession and accessibility of information technology devices with respect to the disability profile, and that the disabled have lower possession and accessibility of devices than the non-disabled. Result of this study’s demand forecast shows that about 28% of total respondents are currently using information and communication assistive devices, and a majority (67%) of them answered that the use of assistive devices lend great help to their lives. The proportion of those who have been supported by the government or related organizations with information and communication assistive devices were 36% of the total respondents, and those satisfied with the performance of the devices were 46% of the total responses. Meanwhile, only 36% of total users answered that the operation and use of functions of the devices was easy and convenient, responding that the difficulty of operating assistive devices was the greatest inconvenience. Moreover, the general requests of respondents in regards to the devices were stabilization of device performance, miniaturization of size, simplification of buttons, and reduction of weight.